[INVITED] Coherent perfect absorption of electromagnetic wave in subwavelength structures. (May 2018) - Yan, Chao; Pu, Mingbo; Luo, Jun; Huang, Yijia; Li, Xiong; Ma, Xiaoliang; Luo, Xiangang
Highlights: Basic principles and properties of coherent perfect absorption are discussed. Several CPA-based subwavelength structures are reported. Potential applications of coherent perfect absorption are discussed. Abstract: Electromagnetic (EM) absorption is a common process by which the EM energy is transformed into other kinds of energy in the absorber, for example heat. Perfect absorption of EM with structures at subwavelength scale is important for many practical applications, such as stealth technology, thermal control and sensing. Coherent perfect absorption arises from the interplay of interference and absorption, which can be interpreted as a time-reversed process of lasing or EM emitting. It provides a promising way for complete absorption in both nanophotonics and electromagnetics. In this review, we discuss basic principles and properties of a coherent perfect absorber (CPA). Various subwavelength structures including thin films, metamaterials and waveguide-based structures to realize CPAs are compared. We also discuss the potential applications of CPAs.